L’importance de la forêt résiduelle pour conserver les communautés fauniques dans des paysages boréaux perturbés par la coupe forestière. - Jean Ferron; Martin-Hugues St-Laurent (VertigO, 2005)
The analysis of short-term effects of clear-cutting on wildlife in the boreal forest has shown that areas that have recently been logged are avoided by most of the studied species, with the exception of some small rodents. Most animals moved to the undisturbed neighbouring forest stands. Considering the importance of residual forest for wildlife, the suitability of residual forest has been evaluated using different types of residual forest structures (RFS) varying in size and configuration. Forest strips 60 to 100-m wide were poorly suitable for some studied species, while residual blocks of 18 to 50 ha were more appropriate. Residual forest structures resulting from mosaic (85-100 ha) and mega-blocks (250-300 ha) strategies appeared more adapted to mammal and bird communities conservation, supporting population levels similar to undisturbed mature stands. With such large size of residual forest (85-300 ha), our results showed that structure and composition of residual forest stands, along with landscape configuration, were more important for wildlife than the size of RFS.